Fetal Undernutrition Programming, Sympathetic Nerve Activity, and Arterial Hypertension Development - Mariano, Vinícius Schiavinatto; Boer, Patrícia Aline; Gontijo, José Antônio Rocha (Frontiers in Physiology, 2021)
There is a wealth of evidence that low birth weight is associated with environmental disrupts during gestation, which triggers embryo/fetal adaptation responses and increases adult progeny's susceptibility to developing non-communicable diseases, including metabolic and cardiovascular diseases, obesity and arterial hypertension. By the way, dietary disturbance during pregnancy in animal models has highlighted mechanisms that involve the genesis of arterial hypertension, particularly severe maternal low-protein intake (LP). Functional studies demonstrated that maternal low-protein intake leads to the renal decrease of sodium excretion and dysfunction of renin-angiotensin-aldosterone system signaling of LP offspring. The antinatriuretic effect is accentuated by a reduced number of nephron units, which are critical in establishing arterial hypertension phenotype. Also, in this way, studies have shown that the central and peripheral sympathetic nervous system's overactivity occurs as a consequence of reduced sensory (afferent) renal nerve activity. As a result of this reciprocal and abnormal renorenal reflex, there is an enhanced tubule sodium proximal sodium reabsorption, which, at least in part, contributes directly to arterial hypertension development in some of the programmed models. A recent study has observed that significant changes in adrenal medulla secretion (unpublished data) could be involved in the pathophysiological process of increasing blood pressure. Thus, this review aims to compile studies that link the central and peripheral sympathetic system activity mechanisms on water and salt handle and blood pressure control in the maternal protein-restricted offspring. Besides, these pathophysiological mechanisms mainly may involve the modulation of neurokinins and catecholamines pathways.